Microencapsulation of Deer Oil in Soy Protein Isolate–Chitosan Complex Coacervate—Preparation, Characterization, and Simulated Digestion - Hongyan Li; Ying Zong; Weijia Chen; Yan Zhao; Jianan Geng; Zhongmei He; Rui Du (Foods)
Deer oil (DO) is a potentially beneficial functional oil; however, its sensitivity to environmental factors (e.g., oxygen and heat), difficulty in transport, and unfavorable taste hinder practical use. In this study, DO was encapsulated through the cohesive action of soy protein isolate (SPI) and chitosan (CS). The optimal preparation conditions yielded microcapsules with DO’s highest encapsulation efficiency (EE) (85.28 ± 1.308%) at an SPI/CS mixing ratio of 6:1 and a core-to-wall ratio of 1:2 at pH 6. Fluorescence and scanning electron microscopy were utilized to examine the microcapsules’ structure, showing intact surfaces and effective encapsulation of oil droplets through SPI/CS composite coalescence. Through Fourier transform infrared spectroscopy (FTIR), the electrostatic interplay between SPI and CS was verified during the merging process. At room temperature, the microcapsules resisted core oxidation by reducing gas permeation. In vitro simulated digestion results indicated the microcapsules achieved a slow and sustained release of DO in the intestinal tract. This study further expands the application scope of deer oil and promotes the development of deer oil preparations and functional foods.